Online English Learning at Junior High School: How the Students Perceive Schoology as Learning Media - Muhammad Iksan; Amalia Yahya; Magfirah Thayyib; Bahrul Ilmi (Research and Education Development (READ) Institute collaborate with Faculty of Education and Teacher Training of IAIN Palopo, 2022)
This study focused on the Students' Perception of Schoology Application in Learning English at SMPN 1 Palopo. This study occupied a descriptive qualitative design that spent one-month collecting data using interviews. The data were then reduced, presented, and verified before describing the data in analyzing the interview results. This study revealed that the students reported their positive perception toward Schoology Application in Learning English at SMPN 1 Palopo. The students' positive judgments are based on their experience in learning English by using the Schoology application. They enjoyed the learning process when the teacher practiced Online Learning Method using Schoology. This study also reported that the Schoology application is very beneficial for them. The Schoology application made them more interested in learning. In addition, the application made them more active and responsible in learning.